Grafting polymer from oxygen-vacancy-rich nanoparticles to enable protective layers for stable lithium metal anode. (October 2020) - Li, Sipei; Liu, Tong; Yan, Jiajun; Flum, Jacob; Wang, Han; Lorandi, Francesca; Wang, Zongyu; Fu, Liye; Hu, Leiming; Zhao, Yuqi; Yuan, Rui; Sun, Mingkang; et al.
Abstract: Fabricating an artificial solid electrolyte interface (SEI) is a promising approach to improve cycling stability of lithium metal batteries. In this work, a new category of artificial SEI based on oxygen vacancy-rich hybrid nanoparticles was prepared by covalently grafting polymers from yttria–stabilized zirconia (YSZ) nanoparticles via surface-initiated atom transfer radical polymerization (SI-ATRP). The hairy nanoparticles had high dispersibility in dimethylsulfoxide, and were solution casted into uniform thin films with high inorganic content, high ionic conductivity (>1 × 10 −4  S/cm at r.t.), and good mechanical properties (Young's modulus 7.56 GPa). No dendrite formation was observed by in-situ optical microscopy on a lithium metal protected by such artificial SEI. Protected anodes were stably cycled at 3 mA/cm 2 and 3 mA h/cm 2 with low overpotentials (20 mV) for >2500 h. LiNi0.8 Co0.15 Al0.05 O2 (NCA)|Li full cells with protected Li anode showed much higher specific discharge capacity at various rates and improved capacity retention compared to unprotected Li anode. Graphical abstract: An artificial SEI was prepared by covalent grafting of well-defined polyacrylonitrile from the surface of oxygen vacancy-rich YSZ nanoparticles using ATRP. Such artificial SEI had high inorganic content, high ionic conductivity (>1 × 10 −4  S/cm at r.t.) and very good mechanical properties (Young's modulus 7.56 GPa), enabling dendrite-free deposition for lithium metal anode. Image 1 Highlights: Novel surface-initiated ATRP was applied to covalently graft polymers from oxygen vacancy-rich YSZ nanoparticles. YSZ- g -PAN hybrids showed high solvent dispersity, high ionic conductivity (>10 −4  S/cm, r.t.) and Young's modulus of 7.56 GPa. YSZ- g -PAN artificial SEI on Li metal enabled dendrite-free cycling at 3 mA/cm 2 with areal capacity of 3 mA h/cm 2 for ~2500 h. The protected lithium metal anode showed improved cycling performance with a thick high mass loading NCA cathode.